Course on tunnel construction and design. 13-17 September 1999, Royal Holloway University of London, Egham Surrey. (Thomas Telford, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a course held at Royal Holloway University of London, Egham on 13-17 September 1999.